GE_GERICHTE P/15564/2022 vom 5. Dezember 2022 - GE Cour de justice (2022)
PLAINTE PÉNALE;ACTION PÉNALE;RENONCIATION(SENS GÉNÉRAL);LÉSION CORPORELLE;DIFFAMATION;PREUVE LIBÉRATOIRE | CPP.310; CPP.304; cpp.305; CPP.120; CP.30.al5; CPP.122; CP.123; CP.173